2007
DOI: 10.1111/j.1600-065x.2007.00513.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of reactive oxygen species and nitric oxide in mast cell‐dependent inflammatory processes

Abstract: Reactive oxygen species (ROS) and reactive nitrogen oxide species (RNOS), including nitric oxide, are produced in cells by a variety of enzymatic and non-enzymatic mechanisms. At high levels, both types of oxidants are used to kill ingested organisms within phagocytes. At low levels, RNOS may diffuse outside cells where they impact the vasculature and nervous system. Recent evidence suggests that low levels of ROS produced within cells are involved in cell signaling. Along with these physiological roles, many … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
142
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(147 citation statements)
references
References 157 publications
(197 reference statements)
4
142
0
1
Order By: Relevance
“…However, it is known that low levels of ROS serve as second messengers in mast cell signaling, leading to degranulation, eicosanoid production, and cytokine secretion [16]. In this view, DJ-1 seems to mediate such "ROS-dependent signaling" in mast cells.…”
Section: Lyn-sykmentioning
confidence: 99%
“…However, it is known that low levels of ROS serve as second messengers in mast cell signaling, leading to degranulation, eicosanoid production, and cytokine secretion [16]. In this view, DJ-1 seems to mediate such "ROS-dependent signaling" in mast cells.…”
Section: Lyn-sykmentioning
confidence: 99%
“…Recently, a number of studies have reported that stimulation of mast cells through FcεRI causes the production of intracellular reactive oxygen species (ROS); such compounds have been shown to act as second messengers in the signal transduction pathway leading to cytokine synthesis (7)(8)(9). However, neither the source of ROS generated in response to Ag stimulation nor the pathway by which they are generated in Ag-stimulated mast cells is clearly understood.…”
mentioning
confidence: 97%
“…The activation of MC and subsequent degranulation is calcium-dependent and results in elevated ROS levels [25]. It was hypothesized that FD reduced MC degranulation by blocking ROS production and calcium responses.…”
Section: The Effect Of Fd On Non-ige Mediated Induced Ros Activity Anmentioning
confidence: 99%